Asset Management Information System Perfomance Analysis (SIMASET) Using IT Balanced Scorecard Case Study : Salatiga City Region Revenue Management Unit - Priyanti, Fricila Beti; Wijaya, Agustinus Fritz (Journal of Information System and Informatics, 2021)
Technological developments greatly influence the increasing disruption to the system and system used by the user. Therefore, it is necessary to see how optimal the system is being used by an organization. The Regional Revenue Management Unit (UPPD) of Salatiga City is also inseparable from the development of information technology. By using several information systems, they try to keep up one of the technological developments by using the Asset Management Information System (SIMASET) based website for data collection of goods in and out of the UPPD Salatiga City. In this study using the IT Balanced Scorecard method as a planning solution in terms of performance measurement and monitoring the realization of the value or business benefits and benefits of Information Technology which the IT Balanced Scorecard has four perspectives namely Company Contribution Perspective, User Orientation Perspective, Improvement Perspective Operations and Future Orientation Perspectives. Results and discussion of the 4 Perspectives on Balanced IT Scorecard in this study, it is expected that the User Orientation Perspective and the Future Perspective is doing some improvement because in the User Orientation Perspective the system used often has errors and is quite convoluted in use, the Future Orientation Perspective is almost the same as the User Orientation Perspective, where the quality of the new system still needs to be improved again.